Sequential therapy versus standard triple therapy for Helicobacter pylori eradication in children: any advantage in clarithromycin-resistant strains? - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2014)
Objective There has been a marked decrease in the eradication rates of Helicobacter pylori infection with standard triple therapy worldwide. Hence, sequential therapy has gained attention as a promising treatment during the last few years. This study was carried out to compare the efficacy of sequential versus standard triple therapy in the context of clarithromycin (CLA) resistance. Materials and methods In this study, children between 3 and 18 years of age, who had documented H. pylori infection, were randomized to receive either standard triple or sequential therapy. H. pylori eradication was ascertained using the C-13-urea breath test 4-6 weeks after the completion of the treatment. Real-time PCR was performed on gastric biopsy samples for assessment of CLA resistance. Results In all, 148 children (median age: 12.18 +/- 3.51 years) were recruited randomly into the study. The intention-to-treat eradication rates were 50% (37/74) for the sequential treatment group and 52.7% (39/74) for the standard triple treatment group (P = 0.87). A total of 136 children completed the study. The per-protocol eradication rates were 56% (37/66) and 55.7% (39/70) for sequential and standard triple therapy groups, respectively. CLA resistance was assessed and 113 children were included in the final analysis. Of 113 participants, 53 were in the sequential treatment group and 60 were in the standard triple treatment group. The success rates of the respective therapies (29/53 = 54.7% in sequential, 33/60 = 55% in standard therapy) were similar (P = 0.98). CLA resistance was detected in 29 (25.7%) of the patients. Eradication rates with sequential therapy in CLA susceptible and resistant cases were 60.5% (23/38) and 40% (6/15), respectively (P = 0.23). The corresponding figures for the standard triple treatment group were 63% (29/46) and 28.6% (4/14) (P = 0.033). Although a higher eradication rate was observed in CLA-resistant cases with sequential therapy, the difference did not reach statistical significance (P = 0.69). Conclusion In this study, standard triple treatment failed to eradicate H. pylori infection in the majority of the children, and sequential therapy offered only a small advantage over standard triple therapy in the eradication of CLA-resistant strains. (C) 2014 Wolters Kluwer Health vertical bar Lippincott Williams & Wilkins.
Keywords: antibiotic resistance; children; Helicobacter pylori; sequential; standard; treatment; ANTIBIOTIC-RESISTANCE; RANDOMIZED-TRIAL; CONSENSUS REPORT; INFECTION; METAANALYSIS; MANAGEMENT; GENOTYPES; REGIMEN; SPECIMENS; TRENDS